Breakup season [videorecording (DVD)] - Tracey, H. Nelson; Riggs, Chandler, 1999-; Isler, Samantha; Urbaniak, James, 1963- (Buffalo 8, 2025)
A young man brings his girlfriend to his rural Oregon hometown for Christmas and to meet his family, only for things to go terribly wrong upon arrival. Comedy, drama, and serious heartbreak ensue.